2016
DOI: 10.3390/nu8070396
|View full text |Cite
|
Sign up to set email alerts
|

Mangiferin and Cancer: Mechanisms of Action

Abstract: Mangiferin, a bioactive compound derived primarily from Anacardiaceae and Gentianaceae families and found in mangoes and honeybush tea, has been extensively studied for its therapeutic properties. Mangiferin has shown promising chemotherapeutic and chemopreventative potential. This review focuses on the effect of mangiferin on: (1) inflammation, with respect to NFκB, PPARү and the immune system; (2) cell cycle, the MAPK pathway G2/M checkpoint; (3) proliferation and metastasis, and implications on β-catenin, M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
84
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(93 citation statements)
references
References 86 publications
1
84
0
1
Order By: Relevance
“…Previous pharmacological studies have reported an inhibitory effect of mangiferin on different cancer cell lines such as those from breast cancer, leukaemia, astroglioma, and lung cancer [21]. The anti-tumour effect of mangiferin was primarily attributed to its suppressive effect on inflammation, oxidative stress, and cell-cycle related proteins [22]. Notably, results from a recent study suggested that mangiferin suppressed the active form of β-catenin, an essential element in the activation of the Wnt pathway [23].…”
Section: Introductionmentioning
confidence: 99%
“…Previous pharmacological studies have reported an inhibitory effect of mangiferin on different cancer cell lines such as those from breast cancer, leukaemia, astroglioma, and lung cancer [21]. The anti-tumour effect of mangiferin was primarily attributed to its suppressive effect on inflammation, oxidative stress, and cell-cycle related proteins [22]. Notably, results from a recent study suggested that mangiferin suppressed the active form of β-catenin, an essential element in the activation of the Wnt pathway [23].…”
Section: Introductionmentioning
confidence: 99%
“…The major mechanism of action is the inhibition of the NF‐ κ B pathway, down‐regulating inflammation . It also causes cell cycle arrest, reduces the proliferation/metastasis of cancer cells, promotes apoptosis in malignant cells and protects against oxidative stress and DNA damage …”
Section: Mechanisms Of Actionmentioning
confidence: 99%
“…Compelling evidence demonstrated that mangiferin displays an efficient iron chelating potential (Figure 2), counteracting the hydroxyl radical generation in Fenton reactions [43]. Moreover, the anti-scavenging activity of mangiferin seems to be related to its ability to modulate the Nrf2/ARE (antioxidant response element) signaling detoxification pathway or promote the activation of key detoxifying enzymes [44].…”
Section: Mangiferin: An Unusual Natural Plant Polyphenol By Pleotropimentioning
confidence: 99%